The Effect Of Teams Games Tournament (TGT) Method Towards Students’ English Learning Achievement - Rini Marliana; Dian Novia Isroyana (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
This research aimed at investigating the effect of Teams Games Tournament (TGT) method towards students’ English learning achievement for the eighth grade of MTs. Muallimat NW Kelayu. It was categorized into quantitative research and included in an experimental method. TGT method was applied in the experimental group and another method was applied in control group. In gathering the data, the entire students of the eighth grade comprising 36 students were tested pre-test and post-test. Furthermore, the data was analyzed quantitatively to know the ideal maximum score (SMi), ideal mean (Mi), and ideal deviation score (SDi). Meanwhile, the hypothesis was tested using t-test with the significance level of 0,05 (p=0,05). The result showed that t-test was higher than t-table (3.68>2.02). The alternative hypothesis was accepted. In this case, TGT method has positive effect toward English learning achievement for the students of the eighth grade of MTs. Muallimat NW Kelayu in the school year of 2020/2021